2018
DOI: 10.1002/advs.201801103
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Fe Single Atomic Sites Anchored on Highly Steady Hollow Graphene Nanospheres as an Efficient Electrocatalyst for the Oxygen Reduction Reaction

Abstract: The rational design of economical and high‐performance nanocatalysts to substitute Pt for the oxygen reduction reaction (ORR) is extremely desirable for the advancement of sustainable energy‐conversion devices. Isolated single atom (ISA) catalysts have sparked tremendous interests in electrocatalysis due to their maximized atom utilization efficiency. Nevertheless, the fabrication of ISA catalysts remains a grand challenge. Here, a template‐assisted approach is demonstrated to synthesize isolated Fe single ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 43 publications
1
59
0
1
Order By: Relevance
“…These conventional methods can produce a few layers or even a single layer of graphene, but they are also often susceptible to stacking and aggregation, resulting in a decrease in actual performance. Various special preparation strategies and structures have been reported to prevent the stacking and agglomeration of graphene . In these reports, the design of converting 2D flake graphene into various 3D structures with reasonable design with the help of specific equipment and templates is considered to be an effective solution.…”
Section: Introductionmentioning
confidence: 99%
“…These conventional methods can produce a few layers or even a single layer of graphene, but they are also often susceptible to stacking and aggregation, resulting in a decrease in actual performance. Various special preparation strategies and structures have been reported to prevent the stacking and agglomeration of graphene . In these reports, the design of converting 2D flake graphene into various 3D structures with reasonable design with the help of specific equipment and templates is considered to be an effective solution.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports, which have focused on alkaline anion exchange membrane fuel cells, deeply investigated the ORR activity of Fe-N-C catalysts in alkaline environments, and found that optimizing the preparation procedure boosted catalytic activity and durability. Fe-N-C catalyst obtained by supporting FePc on graphene showed a ORR peak potential in the 0.7-0.84 V vs. RHE in an alkaline environment [22,62,63]. Oliveira et al investigated ORR behaviour in an alkaline electrolyte of FeN 4 macrocycles supported over carbon nanotubes and carbon spheres via a wet impregnation strategy.…”
Section: Contextualization Into Existing Literaturementioning
confidence: 99%
“…The environmental pollution and energy crises have led to great interest in the research and development of environmentally friendly and highly efficient devices that can alleviate these problems . Liquid fuel cells (LFCs) can convert the chemical energy of liquid fuel directly into electrical energy, and therefore, their efficiency is not limited by the Carnot cycle .…”
Section: Introductionmentioning
confidence: 99%